ANALISIS MEDICATION ERROR DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH SANANA KABUPATEN KEPULAUAN SULA - Nurnisa Mayningsih M S Ipa; Gayatri Citraningtyas; Imam Jayanto (UNIVERSITAS SAM RATULANGI, 2023)
Medication error was a disadvantageous activity for patients that in fact could be prevented. This study aimed to know the medication error that occured and find out the percentage of the error in prescribing, transcribing, and dispensing phases at Pharmacy Installation at Sanana Regional General Hospital. This research was observational research approach in which data was compiled prospectively. 369 prescription sheets were recorded at the dispensary of Pharmacy Installation in Sanana Regional General Hospital from March to May 2022. Study findings indicated that the occurrence of medication error in prescribing phase included; no medicinal form at 61.79%, no gender at 34.15%, and no dosage of medicinal form at 6.78%. In transcribing phase, medication error involved; misreading drug names at 4.61%, and misreading the dosage at 1.90%. In dispensing phase, existing medication error included; insufficient drugs at 1.90%. Based on the findings, it could be concluded that medication error occurred in prescribing, transcribing, and dispensing at Sanana Regional General Hospital.Â Â